Comparison of Routine and Concentration Techniques on Microscopic Examination of Stool for Parasitic Ova & Cysts - Wajahat, Muhammad; Sharif, Maryum; Farooq, Hajra (International Journal of Pathology, 2018)
Objective: To compare the routine and concentration techniques on microscopic examination of stool forparasitic ova and cysts to emphasize importance of concentration techniqueMethods: A descriptive study of 100 symptomatic and asymptomatic patients who attended the MicrobiologyLab, Pathology Department, Family Hospital, Rawalpindi a teaching hospital affiliated with Rawalpindi MedicalCollege were studied for six months for stool examination. Three samples from each case at three different dayswere selected not necessarily consecutive. Three techniques were applied on all samples which included directmicroscopic examination by using saline and iodine preparations and the microscopic examination after usingtwo concentration techniques which included simple salt flotation technique and Formal-ether concentrationtechnique.Results: In routine technique 4% of patients were positive for ova/cysts. In saturated saline floatation technique8% of patients were positive for ova/cysts of parasites. In formal ether sedimentation technique also 8%ofpatients were positive.Conclusion: Concentration techniques (formal-ether sedimentation and saturated salt floatation) significantlyimproved the sensitivity from 4% to 8% for detection of ova/cysts of parasites as compared to routine iodinepreparation technique. Although concentration techniques are well known, these need to be implemented inthose laboratories where these are not used.